From crisis to opportunity through innovation (2024)
Purpose This study aims to explore the strategic decisions at innovation level implemented by firms to thrive and transform themselves during crises. This study also aims to provide insights to answer the question: Why do some firms decide to implement certain types of innovation during a crisis? Design/methodology/approach This research was carried out through a multiple case study involving 22 firms. The methods were implemented in three steps to increase rigor and the replication of the study: identification and selection of cases, data collection through interviews triangulated with online information and analysis based on aggregating themes and finding patterns. Findings In the face of the COVID-19 pandemic, the companies analyzed focused their activities mainly on developing new features or functionalities for their products or services. Most of the firms implemented innovations across nearly all ten categories outlined by Keeley et al. (2013). Many of the implemented innovations involved personalized and superior service enhancements, process efficiency optimizations, channel diversification initiatives and new ways to collaborate to generate value. In general, the main drivers that led firms to decide to implement these innovations include reducing costs, enhancing operational efficiency, generating new revenue streams, augmenting sales and enhancing client relationships. Practical implications This research significantly advances the convergence of innovation, strategy and crisis in three impactful ways. First, it constructs a pragmatic and evidence-based framework, consolidating the primary catalysts, innovation categories and strategies adopted by firms in response to the challenges posed by the COVID-19 crisis. Second, it offers insights for guiding decision-making processes related to innovation, presenting actionable recommendations derived from the study’s findings. Thirdly, this study highlights critical perspectives that can guide governmental intervention, facilitating the formulation of more tailored and effective policies to assist companies during crisis periods. Originality/value This study centers on developing countries, specifically examining Colombian firms, considering their unique characteristics and priorities. Surprisingly, there is a scarcity of studies delving into the innovation and transformation of firms during the COVID-19 crisis in nations sharing cultural, economic and political similarities with Colombia.